Goncharov in the twenty-first century - Kleespies, Ingrid; Parts, Lyudmila (Studies in Russian and Slavic literatures, cultures and history., 2021)
"Goncharov in the Twenty-First Century brings together a range of international scholars for a reexamination of Ivan Goncharov's life and work through a twenty-first century critical lens. Contributions to the volume highlight Goncharov's service career, the complex and understudied manifestation of Realism in his work, the diverse philosophical threads that shape his novels, and the often colliding contexts of writer and imperial bureaucrat in the 1858 travel text Frigate Pallada. Chapters engage with approaches from post-colonial and queer studies, theories of genre and the novel, desire, laughter, technology, and mobility and travel"--